Relationship lending and switching costs under asymmetric information about bank types - Niinimäki Juha-Pekka (Springer, 2022)
This theoretical paper extends the pioneering articles on relationship lending (e.g., Sharpe 1990; Rajan 1992; von Thadden 2004) by examining relationship lending and hold-up problems in credit markets when borrowers are identical and banks are different. The results show that existing borrowers are informationally captured by good banks and yield profits to them, but new borrowers are unprofitable. In this market, short-term loan contracts and unsecured loans are optimal while loan commitments should not be used. Further, banks and borrowers have long-term relationships. This paper challenges the standard theories on product quality, reputation and experience goods by introducing scenarios in which good and bad banks can retain their existing borrowers. In the standard theories, consumers leave bad producers and search for good ones.